A importância da contação de histórias como ferramenta metodológica nos anos iniciais do ensino fundamental - Ramalho, Myrelle Santana (Universidade Federal do Tocantins, 2019)
This study focuses on the importance of storytelling in the early years of elementary school. To substantiate this work, a theoretical discussion was conducted with authors that allow us to better compress this study, for example: Abramovich (1995), Bettelheim (2002), Sandroni (1986), Coelho (2000), Freire (1998), Regatieri (2008). These authors show us the importance of bringing the child to the fantasy world through reading, since the fairy tales, as well as other fantastic stories, are indispensable to sharpen the creative imagination and personal formation of the child. The research was carried out at the Municipal Center of Basic Education (CMEB), in Arraias-TO, and the methodology of this research followed a qualitative approach, characterized by a descriptive and exploratory study, and a questionnaire was used to collect Data. In results and considerations, we present the contributions of storytelling in the formation of the student in the initial years of elementary school in a school of the municipal public network in the city of Arraiais – TO.